Pasting behaviour, textural properties and freeze-thaw stability of wheat flour-crude malva nut (Scaphium scaphigerum) gum system - Phimolsiripol Y. (2014)
The effect of replacement of crude malva nut gum (CMG) at 0%, 2.5%, 5%, 7.5% and 10% w/w on pasting behaviour, textural properties and freeze-thaw stability of wheat flour was investigated. Replacement of wheat flour by CMG significantly elevated (p < 0.05) the peak viscosity (128-669 RVU), hot paste viscosity (77-363 RVU), breakdown (51-306 RVU) and final viscosity (157-557 RVU) of wheat flour pastes. Pasting temperature (59-85 °C) of the flour decreased with increasing CMG content. The textural parameters including hardness, springiness, cohesiveness, gumminess and chewiness of the mix gels decreased with higher level of CMG. Freeze-thaw stability measurement revealed that wheat gel mixtures containing higher level (7.5% and 10%) of CMG decreased syneresis more than 80% after 3 freeze-thaw cycles, when compared to non-CMG sample. The rate of syneresis depended on CMG concentration and number of freeze-thaw cycles. The results demonstrated that higher viscosity, softer texture and lower syneresis of wheat gel could be attained using CMG. © 2011 Elsevier Ltd. All rights reserved.